2014
DOI: 10.1097/sle.0b013e31828f6be4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Cholecystectomy in Patients Aged 80 Years and Older

Abstract: LC in octogenarians is a relatively safe procedure that can be performed with low morbidity and mortality rates. The comorbidities and higher ASA scale are major risk factors for postoperative complications in this age group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 15 publications
2
7
0
1
Order By: Relevance
“…The incidence of choledocholithiasis increases with age and the overall risk is higher in elderly patients with severe comorbidities like in our study [19][20][21].…”
Section: Discussionsupporting
confidence: 61%
“…The incidence of choledocholithiasis increases with age and the overall risk is higher in elderly patients with severe comorbidities like in our study [19][20][21].…”
Section: Discussionsupporting
confidence: 61%
“…Some studies suggested that laparoscopic cholecystectomy should be the first line approach in specific categories of patients such as the elderly or pregnant women [ 102 , 103 ]. According to meta-analysis published by de Goede et al, elective laparoscopic cholecystectomy in patients with Child A or B cirrhosis is associated with significantly less postoperative complications, shorter duration of hospitalization and shorter time to resume normal diet compared to open technique [ 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…Некоторые исследования показали, что лапароскопическая холецистэктомия должна быть операцией выбора у определенных категорий пациентов, таких как пожилые люди или беременные женщины [102,103]. Согласно метаанализу, опубликованному B. de Goede и соавт., плановая лапароскопическая холецистэктомия у пациентов с циррозом печени класса А и В по Чайлд-Пью ведет к значительно меньшему количеству послеоперационных осложнений, уменьшению длительности госпитализации и более быстрому возвращению к полноценному питанию по сравнению с открытой операцией [104].…”
Section: утверждение 63 среди пациентов с высоким риском -при наличunclassified
“…Some studies suggested that laparoscopic cholecystectomy should be the first line approach in specific cat-egories of patients such as the elderly or pregnant women [102,103]. According to meta-analysis published by de Goede et al, elective laparoscopic cholecystectomy in patients with Child A or B cirrhosis is associated with significantly less postoperative complications, shorter duration of hospitalization and shorter time to resume normal diet compared to open technique [104].…”
Section: Statement 63 Among High-risk Patients In Those With Child mentioning
confidence: 99%